Identification of rice blast resistance genes Pi-1, Pi-2, Pi-33, Pi-40, Pi-ta, Pi-b - O. V. Shumskaya; N. N. Vozhzhova; O. S. Zhogaleva; A. Yu. Dubina; P. I. Kostylev (Зерновое хозяйство России, 2023)
Rice is a valuable crop used for food throughout the world. To develop modern, productive and disease resistant rice varieties, it is necessary to accelerate the breeding process using molecular biology methods. The purpose of the current study was to identify alleles of six blast resistance genes (Pi-1, Pi-2, Pi-33, Pi-40, Pi-ta and Pi-b) in the selected rice samples using MAS (marker-associated selection method). The objects of the study were 446 breeding rice samples sent to the laboratory of cell breeding for analysis by breeders from the laboratory for rice breeding and seed production of the FSBSI «ARC «Donskoy». Identification of genes in them was carried out differentially and was determined by the pedigree of the samples. In order to determine the alleles of the blast resistance genes Pi-1, Pi-2 and Pi-33, all 446 samples were studied, for the Pi-40 gene there were studied 20 samples, for the Pi-ta gene there were studied 316 samples. For DNA extraction, there was used a Russian-made kit ‘DNA-Extran-3’. PCR was performed using specific primers of the target genes. Identification of reaction products was performed on agarosegels after photographing in ultraviolet light. As a result of the study, there were identified the rice samples which carried from 1 to 5 blast resistance genes in various combinations. There have been identified 14 samples that possess a set of 5 resistance genes, such as 2723, 2724, 2727, 2728, 2729, 2730, 2733, 2735, 2736, 5007, 5671, 5673, 5450/2 and 2450/2. The information obtained from the results of the study could then be used by breeders to use valuable genotypes as donors in crosses, as well as to select promising breeding material resistant to blast disease.